Monitoring Volatile Organic Compounds in Air Using Passive Sampling: Regional Cross-Border Study between N. Macedonia and Kosovo - Vllaznim Mula; Jane Bogdanov; Jasmina Petreska Stanoeva; Lulzim Zeneli; Zoran Zdravkovski (Aerosol and Air Quality Research)
Abstract The aim of the study was to monitor volatile organic compounds (VOCs) in outdoor air in nine cities/towns across the Republic of N. Macedonia and the Republic of Kosovo for nine consecutive months, using the Radiello® passive and diffusive samplers, and gas chromatography-mass spectrometry (GC-MS). In parallel, employing static headspace gas chromatography-mass spectrometry (SHS-GC-MS) technique, VOCs from different types of commercially available gasoline and diesel fuels in the monitored cities were analyzed in order to obtain the chemical profiles and to evaluate the presence of their components in ambient air. GC-MS analyses indicate that the gasoline fuel components (BTEX: benzene, toluene, ethylbenzene, and xylenes) and diesel fuel components (n-undecane, n-dodecane, n-tridecane, n-tetradecane, and other linear alkanes) account for approximately 60% of VOCs in the outdoor air in the sampling sites. The bulk of the VOCs in the all-sampling locations regardless of the season come from fossil fuels (automotive fuels) and only minor fraction comes from biogenic emission which is dominated by monoterpenes. Furthermore, the ratios of benzene to toluene (B/T) and xylenes to ethylbenzene (X/E) were used to assess the origins of VOCs emissions in the outdoor urban air at the monitored sites.